Fast-track Innovation: Area Agencies on Aging Respond to the COVID-19 Pandemic. Issue 4 (3rd July 2020) - Wilson, Traci L.; Scala-Foley, Marisa; Kunkel, Suzanne R.; Brewster, Amanda L.
ABSTRACT: Millions of older Americans depend on services provided by Area Agencies on Aging to support their nutritional, social, and health needs. Social distancing requirements and the closure of congregate activities due to COVID-19 resulted in a rapid and dramatic shift in service delivery modes. Area Agencies on Aging were able to quickly pivot due to their long-standing expertise in community needs assessment and cross-sectoral partnerships. The federal Coronavirus relief measures also infused one billion dollars into the Aging Network. As the pandemic response evolves, Area Agencies on Aging are poised to be key partners in a transformed health system.